Inhibitory AKT2 And Vegr2 Genes Expression of Avicennia Marina Using RT-PCR On Widr Cells - T, Qurrohman,; P.A.Z., Hasibuan,; M, Basyuni, (Asian Journal of Pharmaceutical Research and Development, 2020)
Objectives: To evaluate the activities the anticancer of n-hexane extract of Avicennia marina leaves on WiDr cells in down-regulated of expression of Akt2 and VEGFR2 genes. Methods: Avicennia marina leaves were dried and extracted with n-hexane, analyzed the down-regulated Akt 2 and VEGFR2 expression which was determined the Reverse Transcription Polymerase Chain Reaction (RT-PCR) method. Results:N-hexane extract of Avicennia marina, in which there were down regulated expression Akt 2 and VEGFR2 of 0.43 and 0.50 WiDr cells. N-hexane extract of mangrove leaves has cancer chemoprevention activity with down-regulated on WiDr cells. Conclusions: :N-hexane extract of Avicennia marina leaves had anticancer activity with down-regulated on WiDr cells, suggest that significantly inhibit the expression of Akt2 and VEGFR2 genes.